2013
DOI: 10.1016/j.febslet.2013.04.028
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis R2R3‐MYB transcription factor, AtMYB20, negatively regulates type 2C serine/threonine protein phosphatases to enhance salt tolerance

Abstract: Edited by Michael R. Sussman Keywords:Abscisic acid MYB family Salt stress Type 2C serine/threonine protein phosphatase a b s t r a c tWe have characterized the function of a plant R2R3-MYB transcription factor, Arabidopsis thaliana MYB20 (AtMYB20). Transgenic plants overexpressing AtMYB20 (AtMYB20-OX) enhanced salt stress tolerance while repression lines (AtMYB20-SRDX) were more vulnerable to NaCl than wild-type plants. Following NaCl treatment, the expressions of ABI1, ABI2 and AtPP2CA, which encode type 2C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 32 publications
3
127
0
Order By: Relevance
“…Interestingly, salt-induced expression of PP2C genes (i.e., ABI1, ABI2, HAB1, and HAB2), which are negative regulators of ABA signaling, is repressed in the AtMYB44 overexpression lines. Similar observations were also made with AtMYB20: Its overexpression enhances salt tolerance and represses the expression of ABI1 and ABI2 (Cui et al 2013). AtMYB20 directly binds the MYB recognition sites in the ABI1 promoter.…”
Section: Myb/myc Proteinssupporting
confidence: 77%
“…Interestingly, salt-induced expression of PP2C genes (i.e., ABI1, ABI2, HAB1, and HAB2), which are negative regulators of ABA signaling, is repressed in the AtMYB44 overexpression lines. Similar observations were also made with AtMYB20: Its overexpression enhances salt tolerance and represses the expression of ABI1 and ABI2 (Cui et al 2013). AtMYB20 directly binds the MYB recognition sites in the ABI1 promoter.…”
Section: Myb/myc Proteinssupporting
confidence: 77%
“…This indicates that even a slight variation of miR858a expression in rosette tissue could lead to a much bigger impact on the morphology of the plant where this miRNA is lowly abundant. It is well known that MYB transcription factors play an important role in many developmental processes (Ishida et al, 2007;Reyes and Chua, 2007;McCarthy et al, 2009;Dubos et al, 2010;Cui et al, 2013;Chaonan et al, 2014). Previous studies have found that AtMYB11 modulates overall growth in plants by reducing the proliferation activity of the meristematic cells and delaying plant development, whereas the mutant showed faster development of the inflorescence and initiated more lateral inflorescences and fruits (Petroni et al, 2008).…”
mentioning
confidence: 99%
“…At nuclear level many transcription factors are activated, like MYB20. It was demonstrated MYB20 overexpressed lines are more tolerant to salt in contrast knock-out lines are more sensitive under saline condition (Cui et al, 2013).…”
Section: Nacl Sensing and Genes Defense Activationmentioning
confidence: 99%